Succinic acid production from orange peel and wheat straw by batch fermentations of Fibrobacter succinogenes S85. - Li, Q; Siles, J; Thompson, I (2010)
Succinic acid is a platform molecule that has recently generated considerable interests. Production of succinate from waste orange peel and wheat straw by consolidated bioprocessing that combines cellulose hydrolysis and sugar fermentation, using a cellulolytic bacterium, Fibrobacter succinogenes S85, was studied. Orange peel contains D-limonene, which is a well-known antibacterial agent. Its effects on batch cultures of F. succinogenes S85 were examined. The minimal concentrations of limonene found to inhibit succinate and acetate generation and bacterial growth were 0.01%, 0.1%, and 0.06% (v/v), respectively. Both pre-treated orange peel by steam distillation to remove D: -limonene and intact wheat straw were used as feedstocks. Increasing the substrate concentrations of both feedstocks, from 5 to 60 g/L, elevated succinate concentration and productivity but lowered the yield. In addition, pre-treated orange peel generated greater succinate productivities than wheat straw but had similar resultant titres. The greatest succinate titres were 1.9 and 2.0 g/L for pre-treated orange peel and wheat straw, respectively. This work demonstrated that agricultural waste such as wheat straw and orange peel can be biotransformed to succinic acid by a one-step consolidated bioprocessing. Measures to increase fermentation efficiency are also discussed.